2021
DOI: 10.1007/s12070-021-02710-w
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hearing Status in COVID-19 Patients: A Multicentered Review

Abstract: To evaluate the hearing status of COVID-19 patients and compare with control group. Prospective study carried out in 9 institutes. The pure tone audiogram and impedance audiometry of COVID-19 patients performed initially and at 3 months follow up. The control group consisted COVID-19 negative individuals with no history of ear related diseases. The average of air and bone conduction threshold (AC and BC) were compared between the COVID-19 patients and control group using independent t-test with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The current report showed fewer than 10 per cent of the studies reporting on the presence or absence of these symptoms. [115][116][117][118][119] The current analysis showed asymptomatic infections in almost a fourth of affected children. Previous reviews reported the proportion of asymptomatic infections as 40-45 per cent, 120 while the pooled prevalence of asymptomatic cases was calculated to be 48 per cent by Syangtan et al using a random effect model.…”
Section: Discussionmentioning
confidence: 48%
“…The current report showed fewer than 10 per cent of the studies reporting on the presence or absence of these symptoms. [115][116][117][118][119] The current analysis showed asymptomatic infections in almost a fourth of affected children. Previous reviews reported the proportion of asymptomatic infections as 40-45 per cent, 120 while the pooled prevalence of asymptomatic cases was calculated to be 48 per cent by Syangtan et al using a random effect model.…”
Section: Discussionmentioning
confidence: 48%
“…Six out of eight studies indicated the occurrence of middle ear-related symptoms, which include otalgia and aural fullness. Among the symptoms, otalgia appears to be the most common type of middle ear-related symptom reported in these studies (Bhatta et al, 2021 ; Boroujeni et al, 2021 ; Fidan, 2020 ; Maharaj et al, 2020 ; Raad et al, 2021 ; Wanna et al, 2021). A multicentre study conducted by Bhatta et al ( 2021 ) with 331 participants who were COVID-19 positive reported an incidence of 1.8% for otalgia and 11.4% for aural fullness, while Raad et al ( 2021 ) found that six out of eight participants presented with otalgia.…”
Section: Resultsmentioning
confidence: 91%
“…A multicentre study conducted by Bhatta et al ( 2021 ) with 331 participants who were COVID-19 positive reported an incidence of 1.8% for otalgia and 11.4% for aural fullness, while Raad et al ( 2021 ) found that six out of eight participants presented with otalgia. While some studies have not explained the occurrence of otologic symptoms such as otalgia and aural fullness, which may be linked with the presence of middle ear pathologies at times (Stach & Ramachandran, 2022 ), Bhatta et al ( 2021 ) suspect that these symptoms may be because of the inflammation in the nasopharynx, resulting from dysfunctional eustachian tubes.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the persistence of audio and vestibular dysfunction, Bhatta et al 7 evaluated 331 COVID patients at the time of diagnosis and at 3 months follow-up, and failed to show any significant change in hearing status of COVID-19 patients compared to a control group. Moreover, 3.2% patients had mild conductive hearing loss correlated with nasopharyngeal inflammation, which improved over the course of follow-up.…”
Section: Resultsmentioning
confidence: 99%